Undo the home (Palíndromo, 2022)
This visual essay presents a series of photos showing the process of taking off cement parts that cover a Sabiá nest found in a walk. The construction of this artwork is pervaded by my relationship with my mother, in a coexistence that evokes memories that turned into visual/textual production, in which I intend to blur limits between real and fictional. From internal conversations, in an intimate tone, this text addresses to a mother herself and to the nature where the memories accessed for this writing are set. With Jorge Luis Borges writings, I seek brief dialogues about time and memory, which, associated with Louise Bourgeois’s poetic, articulate fragmented writings about home. Gaston Bachelard brings theoretical contribution to think about home in this imaginary.
Keywords: Memory; Home; Nest; Artistic Process